Kemampuan Pertumbuhan Setek Tanaman Gedi (Abelmoschus manihot L. Medik) - Wilhelmus Warip; H. J. Namserna; Fenny S. J. Asyerem (Fakultas Pertanian Universitas Papua, 2015)
This study aims to determine the growing ability of cuttings derived from the top, middle and bottom branches of the gedi plant. Research conducted ecperimentally by using a randomized block design (RAK), which consists of 3 treatment namely cuttings derived from top, middle and bottom branches of the plant. The results showed that the position of the branch significantly affected the shoot formation time and shoot length, but not to shoots and leaf’s number. Cuttings from top and middle branch performed better vegetative growth than those from the bottom branch.